Evaluation of Acanthamoeba keratitis cases in a tertiary medical care centre over 21 years - Wolfgang List (Nature Portfolio, 2021)
Abstract To report on Acanthamoeba keratitis cases in a tertiary university eye-hospital in Graz, Austria, over a 21-year period. Retrospective study. Parameters included demographics, diagnostics, clinical courses, medical therapies, surgical interventions, secondary complications, and best spectacle-corrected visual acuity (BSCVA). Patient records for 44 eyes of 42 patients were analysed; 2 bilateral infections. Mean age at presentation was 31 ± 13 (16–65) years; contact lenses were used in 41 of 44 eyes (93.2%). Symptoms at initial presentation were mainly pain (41/43, 95.3%) and photophobia (16/43, 37.2%). Most frequent morphological findings were stromal infiltrates (30/44, 68.2%). Diagnosis was mainly confirmed by smears (40/42, 95.2%) and polymerase chain reaction (8/42, 19%). Antiamoebic treatment comprised biguanides and diamidines. Penetrating keratoplasty was performed in 10/44 (22.7%) eyes. Median time from symptom onset to initial visit was 2 (0–26) weeks; median follow-up was 30 (2–1008) weeks. BSCVA improved in 23/36 (63.9%) eyes, remained unchanged in 6/36 (16.7%) eyes and deteriorated in 7/36 (19.4%) eyes. Acanthamoeba keratitis predominantly occurs in young contact lens wearers. Diagnosis should be considered in patients with pain and stromal infiltrates. In the majority of cases, BSCVA can be improved. Early diagnosis and adequate treatment should be implemented to prevent complications.